Potato residue chips as corn replacement in Angus bulls: Effects on carcass characteristics, meat quality, and serum metabolites - Chang-Xiao Shi; Hui-Li Wang; Ying-Qi Li; Muhammad Aziz-ur-Rahman; Si-Yu Zhang; Jia-Jie Deng; Wen-Xi Zhao; Xing-Yue Yi; Yi-Min Zhang; Yang He; Bing-hai Cao; Hua-Wei Su (Food and Humanity, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Urbanization facilitates colonization and reshapes strangler-host networks: the fate of strangler figs in a tropical urban landscape and implications for management - Yu-Xuan Mo; Huang Zou; Hai-Xia Hu; Josep Peñuelas; Zhi-Peng Wang; Bang-Xiao Zheng; Xian-Meng Shi; Su Li; Sujan Balami; Hua-Zheng Lu; Liang Song (Urban Forestry & Urban Greening, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Fluorine migration, solidification, and secondary release mechanisms during high-value utilization of spent carbon cathode and bulk solid wastes - Wang Yongfa; Zhu Jiajing; Zheng Yongxing; Hu Jianhang; Li Kongzhai; Tan Cheng; Su Ruichun; Yu Yong; Wang Hua (Journal of Hazardous Materials, 2026)

A new strategy to enhance the responsiveness of intelligent film to the freshness of chilled pork: UiO-66-TFA as a volatile amine-specific adsorption system - Jiayin Hou; Gege Su; Leyi Li; Xue Pan; Yiheng Deng; Wenhao Luo; Hongtao Lei; Hua Zheng; Zonglin Guo (Food Control, 2026)

Polymer-based room-temperature phosphorescence system with tunable mechanical property - Wanjuan Gao; Mingyue Dong; Hua Feng; Lili Wen; Xinyuan Zhang; Dan Li; Yingchen Duan; Zhongmin Su (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Investigating the temperature-dependent reduction behavior of lump high-phosphorus iron ore in hydrogen - Wu Zhou; Yubo Zeng; Yi Su; Weizhe Jie; Yang Li; Zhiyuan Chen; Hua Zhang; Hongwei Ni; Yongxiang Yang (Journal of Environmental Chemical Engineering, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

A Cross-Domain Mamba Network with joint spatial-frequency learning for robust SAR oil spill detection - Pu Song; Peng Yu; Xiaojing Zhong; Lihua Wang; Yuanrong He; Guangchun Li; Zhanyang Qi; Hua Su (Marine Pollution Bulletin, 2026)

High-performance quantum interconnect between bosonic modules beyond transmission loss constraints - Hongwei Huang; Jie Zhou; Weizhou Cai; Weiting Wang; Yilong Zhou; Yunlai Zhu; Ziyue Hua; Yifang Xu; Lida Sun; Juan Song; Tang Su; Ming Li; et al. (Science Bulletin, 2026)

A BRIGHT platform advances integrated hazard indexing toward actionable control of human pathogenic bacteria in residential buildings - Qisheng Li; Huan Liu; Ling N. Jin; Lumeng Liu; Hua Zhou; Wenmao Zeng; Yingxian Zhai; Tian Chen; Jinyan Yu; Dongdong Su; Juan Lin; Qian Wang; et al. (Building and Environment, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Cyclo(Gly-Tyr) alleviates hypercholesterolemia via modulating gut microbiota: critical roles and mechanisms of Bacteroides and Akkermansia - Jingzhi Chen; Zikang Li; Xinhong Wang; Xinyi Li; Manru Chen; Yan Hua; Ziren Su; Jiannan Chen; Qingfeng Xie; Yucui Li (Food Research International, 2026)

Deep learning-assisted portable fluorescence device for dynamic monitoring of mercury absorption in rice - Meng Hu; Xingyu Long; Kang Mao; Junxia Su; Jiaqi Xue; Wei Ma; Zuoxiang Li; Hua Zhang (Food Chemistry, 2026)

Targeting STING activation in antigen-presenting cells via natural polysaccharide-engineered vesicles for antitumor immunotherapy - Tian-Yang Wang; Lang Zhao; Geng-Hui Feng; Jing-Yun Su; Shao-Hua Zhuo; Yan-Mei Li (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Trade-off analysis between soil organic carbon and maize yield under no-tillage: implication for sustainable cropland management - Mei Liang; Yinghao Su; Hui Xu; Ruonan Li; Aizhen Liang; Yan Zhang; Chuang Li; Jinfeng Ma; Hua Zheng (Journal of Environmental Management, 2026)

Aroma in ‘Munage’ Grape Spirits response to different inoculation strategies of H. uvarum/P. fermentans in mixed fermentation with S. cerevisiae - Jia-Qi Wang; Jia-Liang Hu; Qian-Qian Feng; Yang Zhang; Hong-Yan Zhang; Su-Fang Zhang; Yun-Kui Li; Hua-Feng Yang; Guo-Jie Jin (Food Bioscience, 2026)

Functional traits are plastic in response to intercropping, improving the stability of yield through temporal asynchrony - Hao Yang; Wei-Ping Zhang; Surigaoge Surigaoge; Hua-Sen Xu; Ye Su; Ragan M. Callaway; Long Li (Field Crops Research, 2026)

Dynamics of intestinal organization and microbiota during early development of Procypris mera - Lilong Chen; Junquan Ren; Ye Tian; Xiaoqi Tang; Jingting Yao; Weijun Wu; Zhe Li; Yong Lin; Hua Ye; Yusen Li; Shengqi Su (Aquaculture, 2026)

Body size drives male reproductive success through nest competition and paternal care in the toad Leptobrachium boringii - Raziya Abliz; Wei Zhang; Shuang Liu; Rufeng Xiong; Chunhua Huang; Jun Li; Mian Zhao; Zhirong Gu; Man Su; Wei Liu; Hua Wu (Animal Behaviour, 2026)

Influence of tunnel slope on smoke propagation characteristics and longitudinal ceiling temperature profile in metro carriage fires - Mingxuan Qiu; Yanfeng Li; Zhihe Su; Hua Zhong; Hengxuan Zhao; Haoran Zhu; Xiangyu Gao (Tunnelling and Underground Space Technology, 2026)

Detecting global ocean subsurface density change with high-resolution via dual-task densely-former - Hua Su; Weiqi Xie; Luping You; Sihui Li; Dian Lin; An Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effects of carbonization temperature on the synthesis and antibacterial properties of honeysuckle carbon dots: Application in extending pork shelf life - Leyi Li; Gege Su; Yiheng Deng; Xue Pan; Jiayin Hou; Wenhao Luo; Hua Zheng; Hongtao Lei; Xiangzhen Ge; Zonglin Guo (Food Packaging and Shelf Life, 2026)

Mechanisms of cell death in Klebsiella pneumoniae-induced acute splenic injury in Aquarana catesbeiana - Han Lin; Hua Li; Kesong Chen; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2026)

A single-cell-resolution spatial transcriptomic atlas decodes wheat spike development and yield potential - Xiang Zhang; Yi Peng Wang; Xiehai Song; Liang-Zi Zhou; Haixia Yu; Lei Yang; Yan Kai Wang; Xin Yu Wang; Xin Yan Wan; Yongqi Liu; Yan Shi; Zhiliang Yue; et al. (Molecular Plant, 2026)

Different expansion events of the actin and tubulin gene families within spirotrichean ciliates (Alveolate, Ciliophora) - Hua Su; Zengyu Song; Guoling Chai; Fangfang He; Yize Li; Yuxuan Qian; Xuefen Lu; Qi Zhang; Zhenzhen Yi (Molecular Phylogenetics and Evolution, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

2.6 Ga granitoids in the Eastern Dharwar Craton: amalgamation of micro-crustal blocks and cratonization in the Neoarchaean - Shivani Hulaji; Venkatraman S Hegde; Xian Hua Li; V.N. Vasudev; Li Su; Asim Ranjan Pratihari; Manjunath Paltekar (Journal of Asian Earth Sciences, 2026)

Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

1-NP hijacks endocrine-metabolic checkpoints and disrupts testicular steroidogenesis by suppressing the cAMP-PKA-CREB-HMGCR axis - Xin-xin Zhu; Wei-wei Zhang; Ming-yue Hao; Zheng-ya Chen; Bai-fan Wan; Ming-hui Niu; Xiu-liang Li; Jian-hua Wei; Su-ya Liu; Shuang-ling Mi; Hua Wang; De-xiang Xu; et al. (Toxicology Letters, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

How hydrophobic deep eutectic solvents as liquid-liquid extractants remove Pb2+ from wastewater: Material properties, extraction behavior, and molecular-level mechanism simulation? - Jie Qian; Ying-hua Li; Di Luo; Fei Su; Si-nan Liu; Jun-xiang Wang; Wan-qi Li (Environmental Research, 2025)

Enhanced energy storage performances of (1-x) Ba0.85Ca0.15Zr0.1Ti0.9O3-xBiGaO3 lead-free ceramics and MLCC device via multiscale synergistic optimization strategy - Shangshu Li; Qinghu Guo; Cong Su; Yiren Liu; Zhonghua Yao; Minghe Cao; Hanxing Liu; Hua Hao (Chemical Engineering Journal, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Recovery of iron from vanadium extraction tailings via calcification roasting-magnetizing roasting-magnetic separation - Hang Su; Miao Liu; Rucheng Wang; Jinmao Hua; Minglei Gao; Suxing Zhao; Xin Hou; Lanjie Li; Weizao Liu; Yuntao Xin; Xuewei Lv (Journal of Environmental Chemical Engineering, 2025)

Magnetic CoNi@CN for efficient synergistic removal of tetracycline: Bimetallic electronic synergy and non-radical pathway - Peng Li; Sujuan Chen; Yu Kang; Yu Han; Lianghu Su; Chaoqun Tan; Longjiang Zhang; Saier Wang; Hua Wu (Journal of Environmental Chemical Engineering, 2025)

CSW-SAM: a cross-scale algorithm for very-high-resolution water body segmentation based on segment anything model 2 - Tianyi Zhang; Yi Ren; Weibin Li; Chenhao Qin; Licheng Jiao; Hua Su (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Discovery and Significance of Paleozoic Granite Porphyry in the Haidewula Uranium Deposit, East Kunlun Orogenic Belt, Northwest China - Jian-Hua Duan; Tong Liu; Jia-Wen Dai; Hui-Min Su; Yan-Qiang Li; Shao-Yong Jiang (Journal of Earth Science, 2025)

Fragments of ancient continental lithospheric mantle in the Mogok metamorphic Belt, Northern Myanmar: Re–Os isotope and platinum group element constraints - Qing-Hua Zhang; Bin Su; Yi Chen; Victoria Pease; Tou-Ping Peng; Zhu-Yin Chu; Yi-Bing Li; Kai-Hui Shi; Si Chen (Precambrian Research, 2025)

Halogens-co-mixing strategy for the elucidation of halogen effect in copper-based hybrid luminescent materials - Jialin Zhu; Chen Su; Jiali Fan; Haibo Li; Hua Tong; Wei Liu; Gangfeng Ouyang (Chemical Engineering Journal, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Origin and Geological Significance of the Cambrian–Permian Mafic-Felsic Magmatic Rocks in the Longshenggeng Area of the East Kunlun Orogenic Belt - Hua Li; Hui-Min Su; Haikui Tong; Changhai Luo; Jianxin Zhang; Tao Wang; Wenjun Li; Chaoping Xue; Jiaxiang Dong; Yuying Che; Xiaolin Chen; Xiong Li (Journal of Earth Science, 2025)

Satellite-derived bathymetry in Case II coastal waters during tidal ebb and flow without in-situ data: a case study around Jiaozhou Bay, Yellow Sea - Fanlin Yang; Shaoyu Li; Chao Qi; Dianpeng Su; Xiao Hua Wang; Meng Zhang (International Journal of Remote Sensing, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Assessing the divergent effects of green infrastructure landscape patterns on carbon emission and sequestration in 31 cities across China - Kongming Li; Hao Wang; Xin Zhang; Haohai Su; Jiawei Xu; Xiang Hua (Building and Environment, 2025)

Ionic liquid-grafted MXene composite polymer electrolytes for high-performance solid-state batteries - Zhi Qian; Zhao-Dong Qiu; Rui-Qing Wang; Mei-Tong Wei; An-Min Fei; Zhi-Yi Hu; Hemdan S.H. Mohamed; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2025)

Triphenylphosphine directly knitted porous coordinating hyper crosslinked poly(ionic liquid)s for efficient CO2 fixation into cyclic carbonates - Mengqian Fu; Tianyu Guo; Shuaifei Liu; Wen Liu; Yong Li; Cui Qiao; Yunong Li; Zifeng Yang; Wei Hua; Qian Su; Weiguo Cheng; Suojiang Zhang (Chemical Engineering Journal, 2025)

Interaction Between Hypoxia-Inducible Factor 1-alpha Gene Polymorphism and Helicobacter pylori Infection on Gastric Cancer in a Chinese Tibetan Population - Su-Hua Li; Yan Li; Meng-Jun Zhang; Qi An; Jia-Nan Tao; Xue-Hong Wang (Biochemical Genetics, 2025)

Distinct evolutionary origins and mixed-mode transmissions of methanogenic endosymbionts are revealed in anaerobic ciliated protists - Tingting Hao; Hua Su; Zijing Quan; Ruixin Zhang; Minjie Yu; Jiahui Xu; Jia Li; Song Li; Alan Warren; Saleh A. Al-Farraj; Zhenzhen Yi (Marine Life Science & Technology, 2025)
Methanogenic endosymbionts are the only known intracellular archaeans and are especially common in anaerobic ciliated protists. Studies on the evolution of associations between anaerobic ciliates and their methanogenic endosymbionts offer an excellent opportunity to broaden our knowledge about symbiosis theory and adaptation of eukaryotes to anoxic environments. Here, the diversity of methanogenic endosymbionts was analyzed with the addition of nine anaerobic ciliate populations that were newly studied by various methods. Results showed that diverse anaerobic ciliates host methanogenic endosymbionts that are limited to a few genera in orders Methanomicrobiales, Methanobacteriales, and Methanosarcinales. For the first time, anaerobic ciliates of the classes Muranotrichea and Prostomatea were found to host methanogenic endosymbionts. Distinct origins of endosymbiosis were revealed for classes Armophorea and Plagiopylea. We posit that armophoreans and plagiopyleans might have harbored Methanoregula (order Methanomicrobiales) and Methanocorpusculum (order Methanomicrobiales), respectively, as methanogenic endosymbionts at the beginning of their evolution. Subsequently, independent endosymbiont replacement events occurred in methanogen-ciliate associations, probably due to ecological transitions, species radiation of ciliate hosts, and vertical transmission bottlenecks of endosymbionts. Our results shed light on the evolution of associations between anaerobic ciliates and methanogens, and identifies the necessary preconditions for illustrating mechanisms by which endosymbioses between these partners were established.

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Thioclava kandeliae sp. nov., Isolated from the Rhizosphere Soil of Mangrove Plant Kandelia candel - Tong Mou; Jing Su; Jing Zhang; Li-Yan Yu; Hua-Hong Chen; Yu-Qin Zhang (Current Microbiology, 2025)

Mechanism of spillage plumes from multiple openings on ceiling temperature distribution in metro tunnel fires based on superposition principle - Zhihe Su; Yanfeng Li; Runzhou Luo; Hua Zhong; Junmei Li; Zhihao Geng; Zhicheng Guo (Tunnelling and Underground Space Technology, 2025)

Compositional complexity of heterogeneous impact glasses in lunar soils: significance and pitfalls - Qian W. L. Zhang; Bin Su; Pierre Lanari; Jia-Hui Liu; Jia-Long Hao; Yu Liu; Liu-Yang Chen; Di Zhang; Jiang-Yan Yuan; Juan Wang; Xian-Hua Li; Qiu-Li Li (Contributions to Mineralogy and Petrology, 2025)
Heterogeneous impact glass beads are abundant in lunar soils and have been extensively used to study the geological processes that shaped the Moon’s surface. In this study, we examine the compositional complexity of three heterogeneous glass beads containing undigested zirconolite and zircon, using EPMA, Nano-SIMS mapping, and SIMS U–Pb isotope analyses. The undigested zircon and zirconolite crystals document three key volcanic events in the lunar history: at ~ 4.31 Ga the formation of alkali-suite rocks from the highlands, and at ~ 3.92 Ga, and ~ 2.04 Ga mare basalts, indicating that the U–Pb system in these zirconium-bearing crystals remains undisturbed during the ultra-high-temperature, short-duration impact melting events. EPMA and Nano-SIMS mapping reveal significant compositional inhomogeneity in the glass matrices, which complicates accurate provenance determination based on in-situ analysis. Bulk composition calculated from quantitative maps, however, provides a more reliable reference for inferring the origins of these beads. The high proportions of common Pb in the heterogeneous glass matrices, originating from diffusion-controlled processes during partial melting of impact involved minerals, introduce substantial uncertainties in U–Pb dating, complicating the interpretation of impact event ages. These findings highlight the challenges of U–Pb dating in heterogeneous glass beads and provide new insights into the preservation of pristine age information in lunar impact materials.

Enhanced virulence of Acinetobacter johnsonii at low temperatures induces acute immune response and systemic infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Jingyang Sun; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Veterinary Microbiology, 2025)

Continuous-flow organic pollutants degradation via periodate activation with a self-assembled MnOx-based catalytic membrane reactor - Yiping Su; Yangke Long; Gang Li; Han Hua; Zuotai Zhang (Journal of Water Process Engineering, 2025)

PD-like pathogenesis induced by intestinal exposure to microplastics: An in vivo study of animal models to a public health survey - Hua Bai; Huan Gu; Wenhui Zhou; Guolin Shi; Jinyuan Yan; Yanmei Su; Wenhu Li; Yixin Li; Chidi Zhong; Ninghui Zhao; Xiaowei Huang (Journal of Hazardous Materials, 2025)

Safety and antioxidant assessments of BLR-E50, 50% ethanolic extract from red beans co-fermented by Bacillus subtilis and Lactobacillus bulgaricus - Su-Tze Chou; Yi-Hua Chen; Yi-Hung Chen; Yu‐Chen Tsai; Yun-Chin Chung; Ju-Pi Li (Food and Chemical Toxicology, 2025)

Current status and strategies for controlling hexachlorobutadiene from multiple perspectives of emission, occurrence, and disposal - Xin Li; Mujie Wang; Meifang Hou; Guijin Su; Bohua Sun; YuKang Hua; Jiaxin Pang; Jing Meng; Bin Shi; Qianqian Li (Environmental Research, 2025)

Green extraction of α-nitroso-β-naphthol from wastewater using hydrophobic deep eutectic solvents: A comprehensive study of efficiency and mechanism - Jie Qian; Ying-hua Li; Di Luo; Si-nan Liu; Fei Su; Jun-xiang Wang (Environmental Pollution, 2025)

Energy, economic, emissions analysis of semi-flexible crystalline silicon photovoltaic system integrated with factory building roofs based on actual electricity load and cost conditions - Hua Zhang; Xinzhu Chen; Wenxin Li; Ruili Peng; Jie Ji; Xiaoxiao Su; Chenglong Luo (Energy and Buildings, 2025)

Design and study of anti-blocking type potato stubble disc clamping and pulling device based on MBD-DEM coupled simulation - Yewei Wang; Zhongcai Wei; Guoliang Su; Xiangcai Zhang; Xianliang Wang; Xiupei Cheng; Faming Wang; Xueqiang Li; Hua Zhou; Zhenyu Yang; Chengqian Jin (Computers and Electronics in Agriculture, 2025)

Intelligent sensing platform based on europium-doped carbon dots for dual-functional detection of ciprofloxacin/Ga3+ and its tracking in vivo - Le Liang; Su-qian Cai; Yan-li Leng; Chan Huang; Yong-qing Liu; Ye Wang; Li Luo; Mei Han; Xiao-hong Li; Xiao-hua Cai (Journal of Hazardous Materials, 2025)

Regional disparities in PPCPs contamination of urban wastewater treatment plants: Unveiling influential factors and ecological effects - Xing Chen; Xiaofei Lu; Jiahua Peng; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Ming Hu; Bin Shi (Environmental Pollution, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Sealing Integrity Evaluation and Optimization of Cement Sheath-Formation Interface under Different Formation Conditions during Fracturing - Donghua Su; Sheng Huang; Zaoyuan Li; Jin Li; Ziyu Wang; Shizhong Tang; Hua Wu; Bo Zhao (Journal of Earth Science, 2025)

High entropy oxides as a rising star in pollutant disposal and resource recycling: Emerging advancements and future challenges - Yukang Hua; Guijin Su; Qianqian Li; Jiaxin Pang; Bohua Sun; Yue Zhang; Xing Chen; Bin Shi; Jing Meng (Critical Reviews in Environmental Science and Technology, 2025)

A green integrated process for phosphogypsum recycling: CO2 sequestration combined with SO2 recovery - Yi Su; Yang Li; Wu Zhou; Weizhe Jie; Hua Zhang; Hongwei Ni (Journal of Environmental Management, 2025)

Time-dependent responses and modeling of circular steel tube confined reinforced concrete (STCRC) accounting for partial exposure condition - Huan-Chi Ma; Xue-Chang Zhang; Su-Mei Zhang; Xiang Li; Yan-Hua Li; Yue Geng (Engineering Structures, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Evaluating the impact of tunnel slope on critical velocity and confinement velocity in metro tunnel carriage fires - Zhihe Su; Yanfeng Li; Hua Zhong; Junmei Li; Boyu Li; Siyan Kang; Youbo Huang (Tunnelling and Underground Space Technology, 2024)

Evaluation of phytohormone facilitation in microalgal biomass production using mathematical modeling - Zhuo-Xuan Wang; Zi-Ci Su; Guo-Quan Zhou; Yu Luo; Hui-Ran Chen; Zhuo Chen; Xuan Li; Cheng-Yue Liang; Guo-Hua Dao (Science of The Total Environment, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

Investigating dehumidification and heating performance in a dual evaporator heat pump system for electric vehicles - Kang Li; Mingfei Tan; Yuan Man; Hua Zhang; Binlin Dou; Ni Liu; Tianjiao Zhang; Qize He; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Refined one-dimensional modeling and experimental validation of scroll compressor with vapor injection for electric vehicles - Kang Li; Jiayun Hu; Chao Li; Xuejin Zhou; Ni Liu; Hua Zhang; Binlin Dou; Qize He; Ran Tu; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

Discovery of novel Akt1 inhibitors by an ensemble-based virtual screening method, molecular dynamics simulation, and in vitro biological activity testing - Wen Zhang; Mei-Ling Hu; Xiu-Yun Shi; Xiang-Long Chen; Xue Su; Hua-Zhao Qi; Li Yuan; Hui Zhang (Molecular Diversity, 2024)

Occurrence and risks of PPCPs of a typical mountainous region: Implications for sustainable urban water systems - Xing Chen; Xiaofei Lu; Renxin Zhao; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Bin Shi (Science of The Total Environment, 2024)

BrARR10 contributes to 6-BA-delayed leaf senescence in Chinese flowering cabbage by activating genes related to CTK, GA and ABA metabolism - Ci-mei Wang; Ze-xiang Zeng; Zong-li Liu; Jian-hua Zhu; Xin-guo Su; Ri-ming Huang; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

Lappanolides A−N, fourteen undescribed sesquiterpenoids from Saussurea costus (Syn. Saussurea lappa) and their anti HBV activity - Hong-Bo Li; Shi-Qun Bai; Teng-Yun Shu; Qiong Wang; Hao Chen; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Amorphous titanium dioxide and polyaniline dual modifying silicon for highly enhanced lithium-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Meng Wang; Jing Liu; Zhi-Yi Hu; Bei Li; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Biomaterials in heterotopic ossification: Prophylaxis and promotion - Xu Lou; Dan Huang; Guangfeng Li; Long Bai; Jiacan Su; Hua Yue (Chemical Engineering Journal, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Electrical Characteristics of Tangjiawan Landslide in Lixian, Sichuan - Bin Li; Qiang Xu; Qiang Cheng; Tian-Xiang Liu; Jian-hua Yu; Yu-jie Su; Feng Wang (Applied Geophysics, 2024)

Origin of high-Mg# orthopyroxene-rich cratonic mantle: Insights from the Mogok peridotites (Myanmar) - Bin Su; Yi Chen; Stéphane Guillot; Hao-Jie Chen; Yi-Bing Li; Si Chen; Qing-Hua Zhang; Kyaing Sein (Precambrian Research, 2024)

Ameliorating the electronic environment of NiCoP by halogen doping: A strategy for boosting hydrogen evolution performance - Jian Su; Nan Jiang; Bolong Jiang; Yuanyuan Wang; Xueqin Wang; Zhijun Li; Hua Song (Fuel, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Mechanisms and clinical landscape of N6-methyladenosine (m6A) RNA modification in gastrointestinal tract cancers - Dan-Hua Zhu; Kun-Kai Su; Xiao-Xi Ou-Yang; Yan-Hong Zhang; Xiao-Peng Yu; Zu-Hong Li; Seyedeh-Sara Ahmadi-Nishaboori; Lan-Juan Li (Molecular and Cellular Biochemistry, 2024)
Epigenetics encompasses reversible and heritable chemical modifications of non-nuclear DNA sequences, including DNA and RNA methylation, histone modifications, non-coding RNA modifications, and chromatin rearrangements. In addition to well-studied DNA and histone methylation, RNA methylation has emerged as a hot topic in biological sciences over the past decade. N6-methyladenosine (m6A) is the most common and abundant modification in eukaryotic mRNA, affecting all RNA stages, including transcription, translation, and degradation. Advances in high-throughput sequencing technologies made it feasible to identify the chemical basis and biological functions of m6A RNA. Dysregulation of m6A levels and associated modifying proteins can both inhibit and promote cancer, highlighting the importance of the tumor microenvironment in diverse biological processes. Gastrointestinal tract cancers, including gastric, colorectal, and pancreatic cancers, are among the most common and deadly malignancies in humans. Growing evidence suggests a close association between m6A levels and the progression of gastrointestinal tumors. Global m6A modification levels are substantially modified in gastrointestinal tumor tissues and cell lines compared to healthy tissues and cells, possibly influencing various biological behaviors such as tumor cell proliferation, invasion, metastasis, and drug resistance. Exploring the diagnostic and therapeutic potential of m6A-related proteins is critical from a clinical standpoint. Developing more specific and effective m6A modulators offers new options for treating these tumors and deeper insights into gastrointestinal tract cancers.

In-depth impact evaluation of binders on the mechanical properties and CO2 capture performance of CaO-based particles - Xuehua Shen; Ruiheng Zhang; Yiping Su; Han Lin; Feng Xie; Yingying Cai; Guanghuan Li; Jiali Hua; Feng Yan; Zewei Quan; Zuotai Zhang (Journal of Environmental Chemical Engineering, 2024)

Knockdown of the cap ‘n’ collar isoform C gene increases the susceptibility of Agrotis ipsilon to chlorantraniliprole and phoxim - Qing-Hua Xiao; Wu-Ye Li; Jin Zhang; Jia-Min Yu; Dong-Yang Liu; Jiang-Nan Peng; Mao-Ye Li; Su Liu (Journal of Asia-Pacific Entomology, 2024)

Advancements in smoke control strategies for metro tunnel cross-passage: A theoretical and numerical study on critical velocity and driving force - Zhihe Su; Yanfeng Li; Hua Zhong; Junmei Li; Zhicheng Guo; Xin Yang; Shi Yang (Tunnelling and Underground Space Technology, 2024)

A facile method for preparing the CeMnO3 catalyst with high activity and stability of toluene oxidation: The critical role of small crystal size and Mn3+-Ov-Ce4+ sites - Jianshen Wang; Junming Su; Gangguo Zhao; Dan Liu; Hua Yuan; Alex T. Kuvarega; Bhekie B. Mamba; Hu Li; Jianzhou Gui (Journal of Hazardous Materials, 2024)

A comparative study on the nutritional composition, protein structure and effects on gut microbiota of 5 fermented soybean products (FSPs) - Xinyu Miao; Honghong Niu; Mubai Sun; Xin Dong; Mei Hua; Ying Su; Jinghui Wang; Da Li (Food Research International, 2024)

E-eye and FT-NIR combined with multivariate algorithms to rapidly evaluate the dynamic changes in the quality of Gastrodia elata during steaming process - Jiu-ba Zhang; Bin Wang; Yun-fei Zhang; Yi Wu; Ming-xuan Li; Ting Gao; Tu-lin Lu; Zhen-hua Bian; Lian-lin Su (Food Chemistry, 2024)

Liver transcriptome analysis reveal the metabolic and apoptotic responses of Trachinotus ovatus under acute cold stress - Jing Zhang; Qing-Hua Wang; Ben-Ben Miao; Ren-Xie Wu; Qian-Qian Li; Bao-Gui Tang; Zhen-Bang Liang; Su-Fang Niu (Fish & Shellfish Immunology, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Lactate ameliorates palmitate-induced impairment of differentiative capacity in C2C12 cells through the activation of voltage-gated calcium channels - Juan Wan; Chunfang Cheng; Xiaonuo Li; Yuanjie Zhu; Hu Su; Yanchun Gong; Kaizhi Ding; Xiaofei Gao; Caixia Dang; Guoyin Li; Wei Jiang; Li-Hua Yao (Journal of Physiology and Biochemistry, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Lactate induces C2C12 myoblasts differentiation by mediating ROS/p38 MAPK signalling pathway - Chunfang Cheng; Wenxi Li; Yuanqian Ye; Yuanjie Zhu; Mengyuan Tang; Zhihong Hu; Hu Su; Caixia Dang; Juan Wan; Zhibin Liu; Yanchun Gong; Li-Hua Yao (Tissue and Cell, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Iron oxide nanoclusters formed by acid-induced in situ calcium ion cross-linking for targeted magnetic resonance imaging of glioblastoma - Ruoxi Xie; Shengxiang Fu; Guannan Zhu; Hua Ai; Bin Song; Su Lui; Gaocan Li; Yunbing Wang; Min Wu (Chemical Engineering Journal, 2024)

Acute septicemia and diagnostic evaluation of Aeromonas veronii infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Guilian Zeng; Yebing Yu; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

Sesquiterpenoids from aged Artemisia argyi and their 3D-QSAR for anti-HBV activity - Yu-Ying Song; Yong-Zhi Zhou; Yun-Fen Wang; Teng-Yun Shu; Yang Feng; Min Xu; Li-Hua Su; Hai-Zhou Li (Phytochemistry, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Trithiocyanurate-functionalized hydrochar for effectively removing methylene blue and Pb (II) cationic pollutants - Shen-Ao Huang; Hua-Jing Teng; Yin-Tao Su; Xiao-Meng Liu; Bing Li (Environmental Pollution, 2023)

Dry-season irrigation further promotes the growth of Eucalyptus urophylla × E. grandis plantations under the conventional fertilization - Lei Hua; Fei Yu; Quan Qiu; Qian He; Yan Su; Xiaodong Liu; Jiyue Li (New Forests, 2023)

E-eye, flash GC E-nose and HS-GC-MS combined with chemometrics to identify the adulterants and geographical origins of Ziziphi Spinosae Semen - Jiu-ba Zhang; Ming-xuan Li; Yun-fei Zhang; Yu-wen Qin; Yu Li; Lian-lin Su; Lin Li; Zhen-hua Bian; Tu-lin Lu (Food Chemistry, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Development and validation of a machine learning model to predict prognosis in HIV-negative cryptococcal meningitis patients: a multicenter study - Junyu Liu; Yaxin Lu; Jia Liu; Jiayin Liang; Qilong Zhang; Hua Li; Xiufeng Zhong; Hui Bu; Zhanhang Wang; Liuxu Fan; Panpan Liang; Jia Xie; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Macrocyclic lactone residues in cattle dung result in a sharp decline in the population of dung beetles in the rangelands of northern China - Hua Su; Hong Xu; Benying Su; Wei Liu; Yingfei Cao; Yonggeng Li (Agriculture, Ecosystems & Environment, 2023)

Corrigendum to “Maternal linuron exposure alters testicular development in male offspring rats at the whole genome level” [Toxicology 389 (2017) 13–20] - Jianwei Bai; Hua Han; Feng Wang; Liyu Su; Hongwei Ding; Xiyin Hu; Binli Hu; Hong Li; Wei Zheng; Yan Li (Toxicology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Low Ni and Co olivine in Chang’E-5 basalts reveals the origin of the young volcanism on the Moon - Bin Su; Di Zhang; Yi Chen; Wei Yang; Qian Mao; Xian-Hua Li; Fu-Yuan Wu (Science Bulletin, 2023)

Single-atom Ce targeted regulation SnS/SnS2 heterojunction for sensitive and stable room-temperature ppb-level gas sensor - Long Li; Huyin Su; Licheng Zhou; Zhixiang Hu; Tiankun Li; Bingbing Chen; Hua-Yao Li; Huan Liu (Chemical Engineering Journal, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Identification and expression characteristics of NLP (NIN-like protein) gene family in pepper (Capsicum annuum L.) - Yuan Wu; Shi-xian Su; Tao Wang; Gui-Hua Peng; Lei He; Cha Long; Wei Li (Molecular Biology Reports, 2023)

Indoor air quality and its health effects in offices and school buildings in the Yangtze River Delta - Chanjuan Sun; Jingyu Chen; Shijie Hong; Yinping Zhang; Haidong Kan; Zhuohui Zhao; Furong Deng; Xiangang Zeng; Yuexia Sun; Hua Qian; Wei Liu; Jinhan Mo; et al. (Air Quality, Atmosphere & Health, 2023)

Artemiprinolides A−M, thirteen undescribed sesquiterpenoid dimers from Artemisia princeps and their antihepatoma activity - Li-Hua Su; Wen-Jing Ma; Yun-Bao Ma; Tian-Ze Li; Chang-An Geng; Wei Dong; Xiao-Feng He; Ji-Jun Chen (Phytochemistry, 2023)

Four ciliate-specific expansion events occurred during actin gene family evolution of eukaryotes - Hua Su; Jiahui Xu; Jia Li; Zhenzhen Yi (Molecular Phylogenetics and Evolution, 2023)

The influences of the oil circulation ratio on the performance of a vapor injection scroll compressor in heat pump air conditioning system intended for electrical vehicles - Kang Li; Jingru Ma; Jian Cao; Bin Zhang; Binlin Dou; Ni Liu; Hua Zhang; Lin Su; Xuejin Zhou; Ran Tu (International Journal of Refrigeration, 2023)

Spatio-temporal variation of soil microplastics as emerging pollutant after long-term application of plastic mulching and organic compost in apple orchards - Yuanji Wang; Li Liu; Shan Cao; Jing Yu; Xiangyu Li; Yating Su; Gaochao Li; Hua Gao; Zhengyang Zhao (Environmental Pollution, 2023)

Ubiquitinomics revealed disease- and stage-specific patterns relevant for the 3PM approach in human sigmoid colon cancers - Hua Yang; Na Li; Liang Chen; Lei Zhou; Yuanchen Zhou; Jixiang Liu; Wenshuang Jia; Ruofei Chen; Junwen Su; Lamei Yang; Xiaoxia Gong; Xianquan Zhan (EPMA Journal, 2023)

An amine-modified Pd-based catalyst for highly-efficient 2-amylanthraquinone hydrogenation - Hua Yan; Xiaowei Liu; Junhong Zhou; Dawei Li; Xiaoye Yang; Yiming Gu; Hongjiu Su; Shudong Wang (Fuel, 2023)

Simultaneously achieving enhanced water adsorption and rapid adsorbed hydroxyl transfer toward MXene-based materials for highly efficient alkaline electrocatalytic hydrogen evolution - Yang Meng; Ping Zeng; Xiao-Yu Yang; Zhan Liu; Xiao-Yun Li; Cui-Fang Ye; Yu Li; Jin-Ping Liu; Bao-Lian Su; Li-Hua Chen; Yi-Long Wang (Chemical Engineering Journal, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Accumulation and re-distribution of microplastics via aquatic plants and macroalgae - A review of field studies - Sirui Huang; Ruitong Jiang; Nicholas J. Craig; Hua Deng; Wenhui He; Juan-Ying Li; Lei Su (Marine Environmental Research, 2023)

Comprehensive phylogenomic analyses reveal that order Armophorida is most closely related to class Armophorea (Protista, Ciliophora) - Jia Li; Song Li; Hua Su; Minjie Yu; Jiahui Xu; Zhenzhen Yi (Molecular Phylogenetics and Evolution, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

A microdots array-based fluoremetric assay with superwettability profile for simultaneous and separate analysis of iron and copper in red wine - Chenchen Xu; Qingqing Liu; Su Chu; Pan Li; Fengxiang Wang; Yanmei Si; Guojiang Mao; Choufei Wu; Hua Wang (Analytica Chimica Acta, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Cost–benefit analysis of reusable takeaway food containers usage: a case on campus in China - Ruijuan Li; Yuanchun Zhou; Hongyan Su; Qi Wang; Hua Wang (Environmental Science and Pollution Research, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

An innovative strategy to control Microcystis growth using tea polyphenols sustained-release particles: preparation, characterization, and inhibition mechanism - Lixiao Ni; Jiajia Wang; Yuanyi Fang; Chengjie Zhu; Jakpa Wizi; Zhiyun Jiang; Cunhao Du; Shiyin Li; Xuqing Chen; Jian Xu; Hua Su (Environmental Science and Pollution Research, 2023)

Time-frequency analysis framework for understanding non-stationary and multi-scale characteristics of sea-level dynamics - Xindan Liang; Yinyi Lin; Renguang Wu; Gang Li; Nicole Khan; Rui Liu; Hua Su; Shan Wei; Hongsheng Zhang (Frontiers in Marine Science, 2023)
Rising sea level caused by global climate change may increase extreme sea level events, flood low-lying coastal areas, change the ecological and hydrological environment of coastal areas, and bring severe challenges to the survival and development of coastal cities. Hong Kong is a typical economically and socially developed coastal area. However, in such an important coastal city, the mechanisms of local sea-level dynamics and their relationship with climate teleconnections are not well explained. In this paper, Hong Kong tide gauge data spanning 68 years was documented to study the historical sea-level dynamics. Through the analysis framework based on Wavelet Transform and Hilbert Huang Transform, non-stationary and multi-scale features in sea-level dynamics in Hong Kong are revealed. The results show that the relative sea level (RSL) in Hong Kong has experienced roughly 2.5 cycles of high-to-low sea-level transition in the past half-century. The periodic amplitude variation of tides is related to Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO). RSL rise and fall in eastern Hong Kong often occur in La Niña and El Niño years, respectively. The response of RSL to the PDO and ENSO displays a time lag and spatial heterogeneity in Hong Kong. Hong Kong's eastern coastal waters are more strongly affected by the Pacific climate and current systems than the west. This study dissects the non-stationary and multi-scale characteristics of relative sea-level change and helps to better understand the response of RSL to the global climate system.

A study of the critical velocity and the confinement velocity of fire accident in a longitudinally ventilated underground train with different door opening scenarios - Zhihe Su; Yanfeng Li; Shan Feng; Hua Zhong; Junmei Li; Wenbo Liu; Chao Chen; Jiaxin Li (Tunnelling and Underground Space Technology, 2023)

Effects of urban particulate matter on gut microbiome and partial schizophrenia-like symptoms in mice: Evidence from shotgun metagenomic and metabolomic profiling - Weizhuo Yi; Yifu Ji; Hua Gao; Shengyong Luo; Rubing Pan; Jian Song; Yangyang He; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoni Sun; et al. (Science of The Total Environment, 2023)

Bacterial cell lysis induced by pre-acidification greatly promoting the degradation of carried antibiotic resistance genes in zero-valent iron activated Fenton-like processes - Xiaoqing Meng; Hua Li; Su Yan; Zengping Ning; Quan Yuan; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Chemical Engineering Journal, 2023)

Citric acid-based deep eutectic solvent (CA-DES) as a new soil detergent for the removal of cadmium from coking sites - Jie Qian; Ying-hua Li; Fei Su; Ji-guo Wu; Jia-ru Sun; Tian-ci Huang (Environmental Science and Pollution Research, 2023)

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Facile one-step synthesis of PhC2Cu nanowires with enhanced photocatalytic performance - Gao-yu Zhao; Hai-yan Li; Yu Yang; Qing-hua Zhao; Ting-ting Su; Jiang-li Ma (Environmental Science and Pollution Research, 2022)

Geomorphic and tectonic controls of landslides induced by the 2022 Luding earthquake - Bo Zhao; Kai-heng Hu; Zong-ji Yang; Qiao Liu; Qiang Zou; Hua-yong Chen; Bo Zhang; Wei-feng Zhang; Lei Zhu; Li-jun Su (Journal of Mountain Science, 2022)

The impact of low-carbon city pilot policy on green total-factor productivity in China’s cities - Ke-Liang Wang; Jin Li; Ru-Yu Xu; Su-Qin Pang; Zhuang Miao; Hua-Ping Sun (Environmental Science and Pollution Research, 2022)

A neglected risk of nanoplastics as revealed by the promoted transformation of plasmid‐borne ampicillin resistance gene by Escherichia coli - Xinxin Wang; Hua Li; Yu Chen; Xiaoqing Meng; Mahlatsi Yorgan Dieketseng; Xiaomeng Wang; Su Yan; Baozhan Wang; Lixiang Zhou; Guanyu Zheng (Environmental Microbiology, 2022)
Plastic pollution and antibiotic resistance are two emerging environmental and human health crises today. Although it was revealed that microplastics can serve as vectors for the dissemination of antibiotic resistance, it is still unclear how the nanoplastics influence the horizontal transfer of antibiotic resistance genes (ARGs). Herein, we firstly compared the effect of polystyrene (PS) micro/nanoplastics on the transformation of plasmid‐borne ARG, using a transformation model consisting of plasmid pUC19 ( amp R ) and Escherichia coli DH5α (recipient). Due to its size effect, PS nanoplastics (10–500 mg/L) significantly enhanced the transformation efficiency (2.8–5.4 folds) and frequency (3.2–8.4 folds) of exogenous amp R into E. coli , while PS microplastics exerted no influence. The detailed mechanisms were found that nanoplastics induced reactive oxygen species (ROS) overproduction, activated SOS response, increased cell membrane permeability and changed the secretion systems, thereby facilitating the uptake of exogenous DNA by bacteria. Moreover, the co‐presences of nanoplastics with humic acid or Fe 3+ relieved to some extent, but did not completely alleviate the promoting effect of nanoplastics on plasmid transformation. Our findings suggest that the risk of nanoplastics on promoting the dissemination of antibiotic resistance should not be neglected, and further studies are needed to investigate such risk in complex environments.

Geochemical constraints of bulk rocks and in-situ zircon from the granitoids of the Hungund Schist Belt: An insight for hydrothermal activity - Shivani Hulaji; V S Hegde; Xian-Hua Li; Li Su; Asim R Pratihari; Manjunath Paltekar (Journal of Earth System Science, 2022)

Effects of Late Pleistocene Climatic Fluctuations on the Phylogeographic and Demographic History of Japanese Scad (Decapterus maruadsi) - Qing-Hua Wang; Ren-Xie Wu; Zhong-Lu Li; Su-Fang Niu; Yun Zhai; Min Huang; Biao Li (Frontiers in Marine Science, 2022)
The Late Pleistocene-Holocene climate fluctuations have greatly influenced the phylogeographic structure and historical dynamics of many marine organisms in the western Pacific marginal seas. Here, we investigated the impact of Pleistocene glacial-interglacial cycles on the phylogeographic structure and demographic dynamics of Decapterus maruadsi , an economically important fish along the coast of the East China Sea (ECS) and northern South China Sea (NSCS). We obtained 430 concatenated sequences (Cyt b + control region, 1548–1554 bp) of D. maruadsi , including 246 newly sampled from the ECS and 184 previously determined from the NSCS. Genetic structure and phylogenetic analysis demonstrated a lack of significant population structure among 16 populations. Moreover, there was no significant differentiation among populations from Chinese coastal waters and northern Vietnam. Neutrality tests, unimodal mismatch distributions, Bayesian skyline plots, and the star-like haplotype networks all indicated a recent demographic expansion for D. maruadsi population during the Late Pleistocene-Holocene, explaining the low genetic diversity in D. maruadsi along the southeast coast of China. Notably, phylogenetic analyses and net genetic distances based on Cyt b jointly confirmed that 57 Cyt b haplotypes identified as D. maruadsi from the previously defined Sundaland-Rosario-Ranong clade actually represented D. russelli . These results not only reveal the complex effects of Pleistocene-Holocene climate fluctuations on the phylogeographic structure and demographic history of D. maruadsi but also provide useful genetic information for the management of genetic resources.

Bone Marrow-Derived Alk1 Mutant Endothelial Cells and Clonally Expanded Somatic Alk1 Mutant Endothelial Cells Contribute to the Development of Brain Arteriovenous Malformations in Mice - Sonali S. Shaligram; Rui Zhang; Wan Zhu; Li Ma; Man Luo; Qiang Li; Miriam Weiss; Thomas Arnold; Nicolas Santander; Rich Liang; Leandro do Prado; Chaoliang Tang; et al. (Translational Stroke Research, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Chromosome-Scale Assembly and Characterization of the Albino Northern Snakehead, Channa argus var. (Teleostei: Channidae) Genome - Chaowei Zhou; Yan Li; Yan Zhou; Yu Zou; Dengyue Yuan; Xingxing Deng; Luo Lei; Jian Su; Chengke Zhu; Hua Ye; Hui Luo; Guangjun Lv; et al. (Frontiers in Marine Science, 2022)
Northern snakehead, Channa argus ( C. argus ), is an important economic and ecological fish species. The wild population of the species was sharply declined in the last decade. A high-quality reference genome could lay a solid foundation for the genetic and conservation studies for C. argus . In this work, we report a chromosomal genome assembly with PacBio and Hi-C technology using the albino northern snakehead, a color variety of C. argus . A 644.1-Mb genome with 24 chromosomes was obtained with a contig and scaffold N50 of 11.78 and 27.8 Mb, respectively. We inferred that C. argus diverged from A. testudineus around 85.6 million years ago. 514 expanded gene families and 214 positively selected genes were identified in the C. argus genome. The chromosome-level genome provides a valuable high-quality genomic resource for population, as well as genetic and evolutionary studies for C. argus and other species in Channidae.

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Species diversity in Penicillium and Acaulium from herbivore dung in China, and description of Acaulium stercorarius sp. nov - Lei Su; Hua Zhu; Peilin Sun; Xue Li; Bochao Yang; Hong Gao; Zhiguang Xiang; Chuan Qin (Mycological Progress, 2021)

LncRNA XIST knockdown alleviates LPS-induced acute lung injury by inactivation of XIST/miR-132-3p/MAPK14 pathway - Chen Li; Jian-Hua Liu; Jing Su; Wei-Jia Lin; Jian-Qing Zhao; Zhi-Hua Zhang; Qi Wu (Molecular and Cellular Biochemistry, 2021)

Genetic dissection of QTLs linked with seedling, yield and fiber quality traits of upland cotton under salt stress field conditions - Ying Su; Shiwei Geng; Anhui Guo; Babar Ijaz; Bin Li; Qin Chen; Kai Zheng; Quanjia Chen; Jinping Hua (Euphytica, 2021)

Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

Inhibition of enterovirus 71 infection by polysaccharides extracted from Picochlorum sp. 122 via the AKT and ATM/ATR signaling pathways - Min Guo; Ruilin Zheng; Hua-lian Wu; Danyang Chen; Jingyao Su; Tiantian Xu; Houbo Wu; Wenzhou Xiang; Yinghua Li; Bing Zhu (Archives of Virology, 2021)

Synergistic inhibitory effect of berberine and icotinib on non-small cell lung cancer cells via inducing autophagic cell death and apoptosis - Ping Chen; Chun-Hua Dai; Zhi-Hao Shi; Yi Wang; Jian-Nong Wu; Kang Chen; Jin-Yu Su; Jian Li (Apoptosis, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Rubus chingii var. suavissimus alleviates high-fat diet-induced lipid metabolism disorder via modulation of the PPARs/SREBP pathway in Syrian golden hamsters - Man-Jing Jiang; Li Li; Wan-Fang Huang; Jian Su; Yao-Hua Li; Xiao-Sheng Qu; Lan-Lan Fan (Journal of Natural Medicines, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

RNA-Seq Transcriptome Analysis of the Liver and Brain of the Black Carp (Mylopharyngodon piceus) During Fasting - Ya-Fan Dai; Yu-bang Shen; Shen-Tong Wang; Jia-Hua Zhang; Yu-Hong Su; Sheng-Chen Bao; Xiao-Yan Xu; Jia-Le Li (Marine Biotechnology, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Spatial distribution and environmental significance of phytoliths in the surface soil of the Xilingol Grassland in Inner Mongolia, China - Chong-Xiao Sun; Hua Su; Cai-Qing Guo; Zhi-Wei Liu; Ya-Meng Li; Feng Qin; Hai-Ming Liu (Palaeobiodiversity and Palaeoenvironments, 2021)

The CMIP6 Historical Simulation Datasets Produced by the Climate System Model CAMS-CSM - Xinyao Rong; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua; Zhengqiu Zhang; Yufei Xin (Advances in Atmospheric Sciences, 2021)
This paper describes the historical simulations produced by the Chinese Academy of Meteorological Sciences (CAMS) climate system model (CAMS-CSM), which are contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6). The model description, experiment design and model outputs are presented. Three members’ historical experiments are conducted by CAMS-CSM, with two members starting from different initial conditions, and one excluding the stratospheric aerosol to identify the effect of volcanic eruptions. The outputs of the historical experiments are also validated using observational data. It is found that the model can reproduce the climatological mean states and seasonal cycle of the major climate system quantities, including the surface air temperature, precipitation, and the equatorial thermocline. The long-term trend of air temperature and precipitation is also reasonably captured by CAMS-CSM. There are still some biases in the model that need further improvement. This paper can help the users to better understand the performance and the datasets of CAMS-CSM.

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

Trajectories of sleep quality and associations with excessive gestational weight gain during pregnancy - Jiajun Lyu; Qingqing Zhu; Shilu Tong; Xiujuan Su; Shenghui Li; Jing Hua (Sleep and Biological Rhythms, 2020)

The association between prenatal endocrine-disrupting chemical exposure and altered resting-state brain fMRI in teenagers - Jun-Cheng Weng; Chi Ieong Hong; Jeng-Dau Tasi; Chao-Yu Shen; Pen-Hua Su; Shu-Li Wang (Brain Structure and Function, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Genome-wide identification, phylogeny, and expression analysis of Sec14-like PITP gene family in sugarcane - Mao Hua-ying; Wang Wen-ju; Su Wei-hua; Su Ya-chun; Liu Feng; Li Cong-na; Wang Ling; Zhang Xu; Xu Li-ping; Que You-xiong (Plant Cell Reports, 2019)

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

An Assessment of CAMS-CSM in Simulating Land–Atmosphere Heat and Water Exchanges - Guo Zhang; Jianduo Li; Xinyao Rong; Yufei Xin; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua (Journal of Meteorological Research, 2018)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Sexual characteristics of male guppies Poecilia reticulata serve as effect biomarkers of estrogens - Hua Tian; Yun Li; Wei Wang; Fei Zhao; Su Gao; Shaoguo Ru (Journal of Oceanology and Limnology, 2018)

An improved indirect ELISA for specific detection of antibodies against classical swine fever virus based on structurally designed E2 protein expressed in suspension mammalian cells - Shengwei Ji; Yuzi Luo; Tengteng Zhang; Lina Shao; Xing-Yu Meng; Yimin Wang; Yao Gao; Yongfeng Li; Su Li; Yuan Sun; Xin Jin; Hua-Ji Qiu (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Compounds with inhibitory activity on peristalsis from the seeds of Holarrhena antidysenterica - Hai-Hua Xie; Jian Su; Xiao-Lei Ge; Ting-Ting Dong; Xin Li; Hui-Min Wen; Bo-Hang Sun (Natural Product Research, 2018)

Activation of Alpha-7 Nicotinic Acetylcholine Receptor Reduces Brain Edema in Mice with Ischemic Stroke and Bone Fracture - Dingquan Zou; Man Luo; Zhenying Han; Lei Zhan; Wan Zhu; Shuai Kang; Chen Bao; Zhao Li; Jeffrey Nelson; Rui Zhang; Hua Su (Molecular Neurobiology, 2017)

Optimal rotation length for carbon sequestration in Eucalyptus plantations in subtropical China - Xiaoguo Zhou; Yuanguang Wen; Uromi Manage Goodale; Hua Zuo; Hongguang Zhu; Xiaoqiong Li; Yeming You; Li Yan; Yong Su; Xueman Huang (New Forests, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

SnRK2 Homologs in Gossypium and GhSnRK2.6 Improved Salt Tolerance in Transgenic Upland Cotton and Arabidopsis - Ying Su; Yumei Wang; Junbo Zhen; Xi Zhang; Zhiwen Chen; Le Li; Yi Huang; Jinping Hua (Plant Molecular Biology Reporter, 2017)

Anti-hepatocellular carcinoma activity of tormentic acid derived from suspension cells of Eriobotrya japonica (Thunb.) Lindl. - Hui-Hua Li; Ming-Hua Su; De-Heng Yao; Bi-Yu Zeng; Qiang Chang; Wei Wang; Jian Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Super absorbent polymer seed coatings promote seed germination and seedling growth of Caragana korshinskii in drought - Li-qiang Su; Jia-guo Li; Hua Xue; Xiao-feng Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Chemical composition of Illicium verum fruit extract and its bioactivity against the peach–potato aphid, Myzus persicae (Sulzer) - Shi-Guang Li; Ben-Guo Zhou; Mao-Ye Li; Su Liu; Ri-Mao Hua; Hua-Feng Lin (Arthropod-Plant Interactions, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Transcriptome analysis provides insights into wood formation during larch tree aging - Wan-Feng Li; Wen-Hua Yang; Shou-Gong Zhang; Su-Ying Han; Li-Wang Qi (Tree Genetics & Genomes, 2017)

Regional selection of the brain size regulating gene CASC5 provides new insight into human brain evolution - Lei Shi; Enzhi Hu; Zhenbo Wang; Jiewei Liu; Jin Li; Ming Li; Hua Chen; Chunshui Yu; Tianzi Jiang; Bing Su (Human Genetics, 2017)

Development of an updated PCR assay for detection of African swine fever virus - Yuzi Luo; Stella A. Atim; Lina Shao; Chrisostom Ayebazibwe; Yuan Sun; Yan Liu; Shengwei Ji; Xing-Yu Meng; Su Li; Yongfeng Li; Charles Masembe; Karl Ståhl; et al. (Archives of Virology, 2017)

Integrin β8 Deletion Enhances Vascular Dysplasia and Hemorrhage in the Brain of Adult Alk1 Heterozygous Mice - Li Ma; Fanxia Shen; Kristine Jun; Chen Bao; Robert Kuo; William L. Young; Stephen L. Nishimura; Hua Su (Translational Stroke Research, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

A triplex real-time PCR for differential detection of classical, variant and Bartha-K61 vaccine strains of pseudorabies virus - Xing-Yu Meng; Yuzi Luo; Yan Liu; Lina Shao; Yuan Sun; Yongfeng Li; Su Li; Shengwei Ji; Hua-Ji Qiu (Archives of Virology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

The impacts of migrant workers consumption on energy use and CO2 emissions in China - Jing-Li Fan; Hua Liao; Bao-Jun Tang; Su-Yan Pan; Hao Yu; Yi-Ming Wei (Natural Hazards, 2016)

Generation and evaluation of a chimeric classical swine fever virus expressing a visible marker gene - Yongfeng Li; Xiao Wang; Yuan Sun; Lian-Feng Li; Lingkai Zhang; Su Li; Yuzi Luo; Hua-Ji Qiu (Archives of Virology, 2016)

The microRNA167 controls somatic embryogenesis in Arabidopsis through regulating its target genes ARF6 and ARF8 - Ying Hua Su; Yu Bo Liu; Chao Zhou; Xiao Ming Li; Xian Sheng Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

A new minor diketopiperazine from the sponge-derived fungus Simplicillium sp. YZ-11 - Bing-Fei Yan; Sheng-Tao Fang; Wen-Zuo Li; Su-Jing Liu; Jian-Hua Wang; Chuan-Hai Xia (Natural Product Research, 2015)

Integrating two layers of soil moisture parameters into the MOD16 algorithm to improve evapotranspiration estimations - Su-Chuang Di; Zhao-Liang Li; Ronglin Tang; Hua Wu; Bo-Hui Tang; Jing Lu (International Journal of Remote Sensing, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

TGF-β1 and TIMP-4 regulate atrial fibrosis in atrial fibrillation secondary to rheumatic heart disease - Yu Sun; Zi-Yang Huang; Zhen-Hua Wang; Cui-Ping Li; Xian-Liang Meng; Yun-Jiao Zhang; Feng Su; Nan Ma (Molecular and Cellular Biochemistry, 2015)

ZAK induces cardiomyocyte hypertrophy and brain natriuretic peptide expression via p38/JNK signaling and GATA4/c-Jun transcriptional factor activation - You-Liang Hsieh; Ying-Lan Tsai; Marthandam Asokan Shibu; Chia-chi Su; Li-Chin Chung; Peiying Pai; Chia-Hua Kuo; Yu-Lan Yeh; Vijaya Padma Viswanadha; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2015)

Water relations and gas exchange of fan bryophytes and their adaptations to microhabitats in an Asian subtropical montane cloud forest - Liang Song; Yong-Jiang Zhang; Xi Chen; Su Li; Hua-Zheng Lu; Chuan-Sheng Wu; Zheng-Hong Tan; Wen-Yao Liu; Xian-Meng Shi (Journal of Plant Research, 2015)

Identification and localized expression of putative K+/H+ antiporter genes in Arabidopsis - Lei Han; Jun Lin Li; Li Wang; Wei Ming Shi; Yan Hua Su (Acta Physiologiae Plantarum, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

Change and Significance of IL-8, IL-4, and IL-10 in the Pathogenesis of Terminal Ileitis in SD Rat - Hong-yu Zhou; Jun Yan; Li Fang; Hui Zhang; Li-guo Su; Guo-hua Zhou (Cell Biochemistry and Biophysics, 2014)

Silencing heat shock protein 27 (HSP27) inhibits the proliferation and migration of vascular smooth muscle cells in vitro - Jie Huang; Liang-di Xie; Li Luo; Su-li Zheng; Hua-jun Wang; Chang-sheng Xu (Molecular and Cellular Biochemistry, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Changes in water use with growth in Ulmus pumila in semiarid sandy land of northern China - Hua Su; Yonggeng Li; Wei Liu; Hong Xu; Osbert Jianxin Sun (Trees, 2014)

Evolution of mitochondrial gene content: loss of genes, tRNAs and introns between Gossypium harknessii and other plants - Binbin Lei; Shuangshuang Li; Guozheng Liu; Zhiwen Chen; Aiguo Su; Pengbo Li; Zhaohu Li; Jinping Hua (Plant Systematics and Evolution, 2013)

Efficient and stable rescue of classical swine fever virus from cloned cDNA using an RNA polymerase II system - Chao Li; Junhua Huang; Yongfeng Li; Fan He; Dan Li; Yuan Sun; Wen Han; Su Li; Hua-Ji Qiu (Archives of Virology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Differences in capacities of in vitro organ regeneration between two Arabidopsis ecotypes Wassilewskija and Columbia - Xiang Yu Zhao; Ying Hua Su; Chuan Li Zhang; Liang Wang; Xing Guo Li; Xian Sheng Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Effects of elevated CO2 on the nutrient compositions and enzymes activities of Nilaparvata lugens nymphs fed on rice plants - YunYun Zeng; WenKun Huang; Li Su; Gang Wu; Jing Zhuang; WanYun Zhao; HongXia Hua; JunSheng Li; NengWen Xiao; YanFei Xiong (Science China Life Sciences, 2012)
Elevated CO 2 may reduce the tolerance of Nilaparvata lugen ( N. lugens ) to adverse environmental factors through the biological and physiological degeneration of N. lugens . In an artificial climate box, under 375 and 750 μL L −1 CO 2 levels, the rice stems nutrient content, the nutrient content and enzyme activities of N. lugens nymph fed on rice seedlings exposed to ambient and elevated CO 2 were studied. The results showed that rice stems had significantly higher protein and total amino acid levels under ambient than elevated CO 2 levels. Nymphs had significantly higher protein levels in the ambient CO 2 treatment, while their glucose levels were significantly lower under ambient CO 2 conditions. Significantly higher trypsin activity was observed in nymphs grown in elevated CO 2 . Significantly lower activities of the protective enzymes total superoxide dismutase and catalase were observed in the nymphs under ambient CO 2 . Meanwhile, the activity of the detoxification enzyme glutathione S-transferase was significantly higher in the ambient CO 2 treatment. Measuring how energy and resources were allocated to enzymes in N. lugens nymphs under elevated CO 2 conditions can provide a more meaningful evaluation of their metabolic tolerances to adverse climatic conditions.

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Selectivity of N170 in the left hemisphere as an electrophysiological marker for expertise in reading Chinese - Jing Zhao; Su Li; Si-En Lin; Xiao-Hua Cao; Sheng He; Xu-Chu Weng (Neuroscience Bulletin, 2012)

Association between the COMT Val158Met polymorphism and breast cancer risk: a meta-analysis of 30,199 cases and 38,922 controls - Xiao-Feng He; Wu Wei; Shao-Xia Li; Jiao Su; Ying Zhang; Xiang-Hua Ye; Yi Liu; Wei Wang (Molecular Biology Reports, 2012)

Chemical and pharmacological studies of Oplopanax horridus, a North American botanical - Tyler Calway; Guang-Jian Du; Chong-Zhi Wang; Wei-Hua Huang; Jing Zhao; Shao-Ping Li; Chun-Su Yuan (Journal of Natural Medicines, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Accurate assessment of antibiotic susceptibility and screening resistant strains of a bacterial population by linear gradient plate - YuQing Liu; JingRan Li; JiaFa Du; Ming Hu; Hua Bai; Jing Qi; Chao Gao; TianTian Wei; Hong Su; JianLing Jin; PeiJi Gao (Science China Life Sciences, 2011)

Development, characterization, and cross-species/genera transferability of SSR markers for rubber tree (Hevea brasiliensis) - Fei Yu; Bao-Hua Wang; Su-Ping Feng; Jing-Yi Wang; Wei-Guo Li; Yao-Ting Wu (Plant Cell Reports, 2011)

Effect of pH on the release of soil colloidal phosphorus - Xinqiang Liang; Jin Liu; Yingxu Chen; Hua Li; Yushi Ye; Zeyu Nie; Miaomiao Su; Zhihong Xu (Journal of Soils and Sediments, 2010)

Cytogenetic analysis of reciprocal hybrids and their parents between Larix leptolepis and Larix gmelinii: implications for identifying hybrids - Shou Gong Zhang; Wen Hua Yang; Su Ying Han; Bo Tao Han; Mao Xue Li; Li Wang Qi (Tree Genetics & Genomes, 2010)

Genetic Diversity and Geographical Differentiation of Desmodium triflorum (L.) DC. in South China Revealed by AFLP Markers - Mao-feng Yue; Ren-chao Zhou; Ye-lin Huang; Guo-rong Xin; Su-hua Shi; Li Feng (Journal of Plant Biology, 2010)

A Mediated Glucose Biosensor Incorporated with Reverse Iontophoresis Function for Noninvasive Glucose Monitoring - Congo Tak-Shing Ching; Tai-Ping Sun; Su-Hua Huang; Hsiu-Li Shieh; Chung-Yuan Chen (Annals of Biomedical Engineering, 2010)

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.

Changes in H2O2 content and antioxidant enzyme gene expression during the somatic embryogenesis of Larix leptolepis - Shou-gong Zhang; Su-ying Han; Wen-hua Yang; Hua-li Wei; Ming Zhang; Li-wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Leaf-level plasticity of Salix gordejevii in fixed dunes compared with lowlands in Hunshandake Sandland, North China - Hua Su; Yonggeng Li; Zhenjiang Lan; Hong Xu; Wei Liu; Bingxue Wang; Dilip Kumar Biswas; Gaoming Jiang (Journal of Plant Research, 2009)

Prevalence of human metapneumovirus in hospitalized children with respiratory tract infections in Tianjin, China - Xiao-yan Li; Jin-ying Chen; Mei Kong; Xu Su; Yan-ping Yi; Ming Zou; Hua Zhang (Archives of Virology, 2009)

A novel endo-glucanase from the thermophilic bacterium Geobacillus sp. 70PC53 with high activity and stability over a broad range of temperatures - I-Son Ng; Chen-Wei Li; Yi-Fang Yeh; Po Ting Chen; Jiun-Ly Chir; Chin-Hua Ma; Su-May Yu; Tuan-hua David Ho; Chii-Gong Tong (Extremophiles, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Characterization of seven genomic and one dbEST-derived microsatellite loci in the river mangrove Aegiceras corniculatum (Myrsinaceae) - Guo-Qing Chen; Lin-Feng Li; Gang Hao; Su-Hua Shi; Xue-Jun Ge (Conservation Genetics, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Observation of amyloid precursor protein cleavage and Aβ generation in living cells by using multiphoton laser scanning microscopy - Xiao-Qing Li; Su-Ming Zhang; Hua-Jing Yang; Zhi-Hong Zhang (Neuroscience Bulletin, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)